Non-linear price transmission between biofuels, fuels and food commodities - Ladislav Krištoufek; Karel Janda; David Zilberman (Charles University in Prague, Institute of Economic Studies (IES), 2013)
For the biofuel markets and related commodities, we study their price transmission, which is in fact equivalent to studying price cross-elasticities. Importantly, we focus on the price dependence of the price transmission mechanism. Several methodological caveats are discussed. Specifically, we combine the memory robust feasible generalized least squares estimation with two-stage least squares to control for endogeneity bias and inconsistency. We find that both ethanol and biodiesel prices are responsive to their production factors (ethanol to corn, and biodiesel to German diesel). The strength of transmission between both significant pairs increased remarkably during the food crisis of 2007/2008.
Keywords: C22; Q16; Q42; 330; biofuels; price transmission; non-linearity